Safety and feasibility of cerebrolysin in treatment of primary intracerebral hemorrhage (CLINCH)—a prospective, randomized, open-label, blinded endpoint pilot trial - Kobayashi, Adam; Rutkowska, Kinga; Gocyla-Dudar, Katarzyna; Chelstowska, Beata; Pozarowszczyk, Natalia; Karlinski, Michal (Frontiers in Neurology, 2025)
BackgroundIntracerebral hemorrhage (ICH) accounts for 15% of strokes with high mortality and limited treatment options. Cerebrolysin, a neuropeptide preparation with multimodal neuroprotective properties, has shown promise in acute ischemic stroke but remains inadequately studied in ICH.MethodsCLINCH is an investigator led, academic driven multicenter, prospective, randomized, open-label, blinded endpoint (PROBE) phase IV pilot study evaluating cerebrolysin in primary lobar ICH. We will randomize 88 patients with lobar ICH (30–80 mL; GCS 8–15; National Institutes of Health Stroke Scale, NIHSS ≥8) within 6 h of onset in a 1:1 ratio to receive either intravenous cerebrolysin (50 mL daily for 14 days) plus standard care including intensive rehabilitation, or standard care alone. Randomization will be stratified by ICH volume (30–50 vs. 51–80 mL) and GCS (8–12 vs. 13–15). Primary endpoints include 90-day mortality (safety) and functional independence (modified Rankin Scale score, mRS 0–2) at 90 days (efficacy). Secondary endpoints include neurological improvement on NIHSS, ordinal mRS shift, Barthel Index, hematoma expansion, and serious adverse events. Blinded assessors will evaluate clinical outcomes, with central adjudication of neuroimaging.DiscussionThis trial addresses critical limitations of previous ICH neuroprotection studies by focusing on lobar hemorrhages, implementing an ultra-early treatment window (≤6 h), and combining neuroprotection with intensive rehabilitation. The restrictive eligibility criteria may limit generalizability but enhance the likelihood of detecting treatment effects. If positive, results would support a larger confirmatory trial and inform the sample size.